(untitled) (Malaysian Journal of Civil Engineering, 2018)
In arid regions the rainfall is highly variable temporally and spatially. Statistical frequency analyses help to extract design rainfall intensity for different return periods. Wadi Alaqiq catchment at Madinah region in the Kingdom of Saudi Arabia is selected to estimate the frequency of the daily rainfall, where there are two rainfall stations (Madinah and BirMashi) with more than 40-year annual maximum daily rainfall magnitudes. Several probability distribution functions are tested through goodness-of-fit (GOF). Anderson-Darling (AD) test is applied to select the best statistical distribution and L-moments method is applied for parameters estimation. The generalized logistic and generalized extreme value PDFs are the best for this arid region data for both stations. The findings are useful for application of flood frequency analysis in arid region with similar conditions of hydrological systems. In the mean-time, the climate change effects have been explained through the innovative trend analysis.